Pendidikan Muslim Tradisional dan Modern di Inti dan Pinggiran: Tantangan yang Bertahan - Purwanto, Budi; Ma’mur, Ilzamuddin; Gunawan, Agus (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2025)
This study explores the dynamics of traditional and modern Islamic education within core and peripheral contexts, examining the challenges faced in a globalized world. The research utilizes qualitative analysis through a combination of literature review and case studies of Islamic educational institutions in both core and diaspora regions. Traditional institutions like pesantren and madrasahs preserve religious and cultural identity but often face criticism for their lack of relevance in modern contexts. The integration of secular curricula in Islamic education is critical for preparing the younger generation to meet global demands. Islamic education in the diaspora faces unique challenges in balancing traditional identity with local values. Moreover, the educational access gap in peripheral areas exacerbates these challenges. The study recommends an integrative educational model that bridges traditional and modern approaches, ensuring the relevance, adaptability, and sustainability of Islamic education. The research aims to offer insights into how educational institutions can adapt to globalization and the changing needs of society.